Improved control strategy for accurate load power sharing in an autonomous microgrid - John, B.; Ghosh, A.; Zare, Firuz; Rajakaruna, Sumedha (The Institution of Engineering and Technology, 2017)
This study proposes a decentralised droop control method for guaranteeing precise load sharing among distributed resources in an islanded microgrid. Distributed resources are usually fed through power electronic converters and the switching harmonics produced by them are eliminated by third-order output LCL filters. Output impedance is considered as a major factor for finding exact power-angle droop coefficient in droop design - neglecting this factor can affect the load sharing accuracy. Even though an acceptable active power sharing can be achieved with higher droop gains, increased droop gain may adversely affect the microgrid stability. Here, a modified angle droop control is proposed such that the dependence on the output inductance on the real power sharing is removed. Thus, the lower droop coefficients are sufficient for droop sharing and the system stability is not endangered. It has been assumed that the microgrid is converter-dominated, where a proportionalresonant controller has been utilised for converter switching control. This controller has an outer voltage loop and an inner current loop. A harmonic term has been added to the voltage loop to facilitate more accurate reactive power sharing. Simulation studies are conducted using PSCAD/EMTDC to validate the efficacy of the proposed controller.